Location and Density of Immune Cells in Precursor Lesions and Cervical Cancer (2013)
ABSTRACT: Only a small proportion of women infected with Human Papillomavirus (HPV) develop cervical cancer. Host immune response seems to play a role eliminating the viral infection and preventing progression to cancer. Characterization of tumor infiltrating lymphocytes (TILs) in cervical pre-neoplastic lesions and cervical cancer may be helpful to understand the mechanisms that mediate this protection. The aim of this study was to determine if there are differences in the localization and density (cells/mm(2)) of CD8+ T-cells, CD4+ T-cells and Tregs (CD25 + Foxp3+) in cervical pre-neoplastic lesions and cervical cancer. Immunohistochemical analysis of sections of 96 (26 CIN1, 21 CIN2, 25 CIN3, and 24 SCC) samples revealed that regardless of CIN grades, CD8+ T-cells are more abundant than CD4+, CD25+ and Foxp3+ cells in both the stroma and epithelium. There was a higher density of CD8+ cells in the stroma of cervical cancer compared to CIN3 (OR = 4.20, 95% CI 1.2-15), CIN2 (OR = 7.86, 95% CI 1.7-36.4) and CIN1 (OR = 4.25, 95% CI 1.1-17). Studies evaluating whether these cells are recruited before or after cancer progression will be helpful to understand the role of these cells in the natural history of HPV-induced lesions.